Enhancing Scientific Literacy through Project-Based Learning in Plant Physiology: A Study of Student-Managed Cultivation Projects - Ria Dwi Jayati; Linna Fitriani (Jurnal Penelitian Pendidikan IPA, 2025)
This study addresses the persistent problem of low scientific literacy among biology education students. It aims to evaluate the effect of project‑based learning (PjBL) through student‑managed plant cultivation on enhancing their scientific literacy. Employing a sequential explanatory design with a mixed‑methods approach, quantitative data were gathered via the Test of Scientific Literacy Skills (TOSLS), while qualitative data were collected through semi‑structured interviews, documentation, and participatory observation. Quantitative analysis showed a significant increase in the mean TOSLS score from 4.43 in the pretest to 9.79 in the posttest (p < 0.001). Corresponding qualitative findings revealed perceived gains in critical thinking, analytical reasoning, and scientific communication, and students reported the experience as authentic and meaningful. In conclusion, PjBL proves effective in facilitating scientific literacy by integrating cognitive, social, and reflective dimensions through real‐world activities such as plant cultivation, offering a robust link between theoretical knowledge and practice in science education.